2015
DOI: 10.1152/ajprenal.00232.2015
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling indirectly affects tubular cell survival after obstructive kidney injury

Abstract: AM, Attanasio M. Hedgehog signaling indirectly affects tubular cell survival after obstructive kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Although the damaged tubular cells may undergo a variety of maladaptive changes such as partial epithelial-mesenchymal transition (EMT), cell cycle arrest, defects in cell metabolism (Grande et al, 2015; Kang et al, 2015; Liu, 2010; Lovisa et al, 2015), one common consequence of these diverse responses is converting to a secretory phenotype (Zhou and Liu, 2016). Indeed, marked induction of Shh protein is observed in the fibrotic kidneys in all commonly used CKD models, including folic acid (FA), unilateral ureteral obstruction (UUO), ischemia reperfusion injury (IRI), adriamycin (ADR) and 5/6 nephrectomy, although it is barely detectable in normal kidneys (Ding et al, 2012; Fabian et al, 2012; Rauhauser et al, 2015; Zhou et al, 2014). In human biopsy specimens, Shh is also specifically induced in renal tubular epithelium of the diseased kidney, regardless of the initial etiologies (Zhou et al, 2014).…”
Section: Shh Signaling and Ckdmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the damaged tubular cells may undergo a variety of maladaptive changes such as partial epithelial-mesenchymal transition (EMT), cell cycle arrest, defects in cell metabolism (Grande et al, 2015; Kang et al, 2015; Liu, 2010; Lovisa et al, 2015), one common consequence of these diverse responses is converting to a secretory phenotype (Zhou and Liu, 2016). Indeed, marked induction of Shh protein is observed in the fibrotic kidneys in all commonly used CKD models, including folic acid (FA), unilateral ureteral obstruction (UUO), ischemia reperfusion injury (IRI), adriamycin (ADR) and 5/6 nephrectomy, although it is barely detectable in normal kidneys (Ding et al, 2012; Fabian et al, 2012; Rauhauser et al, 2015; Zhou et al, 2014). In human biopsy specimens, Shh is also specifically induced in renal tubular epithelium of the diseased kidney, regardless of the initial etiologies (Zhou et al, 2014).…”
Section: Shh Signaling and Ckdmentioning
confidence: 99%
“…This conclusion is also supported by genetic and pharmacologic manipulations of the Shh downstream mediators Smo or Gli proteins. It is shown that the kidneys in Gli1-deficient mice are protected against the development of tubulointerstitial fibrosis after UUO (Ding et al, 2012; Rauhauser et al, 2015). Smo inhibitors such as cyclopamine also repress the induction of Gli1, Snail1 and α-SMA, and reduce matrix expression and mitigate fibrotic lesions in obstructive nephropathy (Ding et al, 2012; Rauhauser et al, 2015), although it does not affect renal Shh expression.…”
Section: Shh Signaling and Ckdmentioning
confidence: 99%
See 3 more Smart Citations